Milk Polar Lipids Affect In Vitro Digestive Lipolysis and Postprandial Lipid Metabolism in Mice. Issue 8 (1st July 2015) - Lecomte, Manon; Bourlieu, Claire; Meugnier, Emmanuelle; Penhoat, Armelle; Cheillan, David; Pineau, Gaëlle; Loizon, Emmanuelle; Trauchessec, Michèle; Claude, Mathilde; Ménard, Olivia; Géloën, Alain; Laugerette, Fabienne; et al.
Abstract: Background: Polar lipid (PL) emulsifiers such as milk PLs (MPLs) may affect digestion and subsequent lipid metabolism, but focused studies on postprandial lipemia are lacking. Objective: We evaluated the impact of MPLs on postprandial lipemia in mice and on lipid digestion in vitro. Methods: Female Swiss mice were gavaged with 150 μL of an oil-in-water emulsion stabilized with 5.7 mg of either MPLs or soybean PLs (SPLs) and killed after 1, 2, or 4 h. Plasma lipids were quantified and in the small intestine, gene expression was analyzed by reverse transcriptase–quantitative polymerase chain reaction. Emulsions were lipolyzed in vitro using a static human digestion model; triglyceride (TG) disappearance was followed by thin-layer chromatography. Results: In mice, after 1 h, plasma TGs tended to be higher in the MPL group than in the SPL group (141 μg/mL vs. 90 μg/mL; P = 0.07) and nonesterified fatty acids (NEFAs) were significantly higher (64 μg/mL vs. 44 μg/mL; P < 0.05). The opposite was observed after 4 h with lower TGs (21 μg/mL vs. 35 μg/mL; P < 0.01) and NEFAs (20 μg/mL vs. 32 μg/mL; P < 0.01) in the MPL group compared with the SPL group. This was associated at 4 h with a lower gene expression of apolipoprotein B ( Apob ) and Secretion Associated, Ras related GTPase 1 gene homolog B ( Sar1b ), in the duodenum of MPL mice compared with SPL mice ( P < 0.05). In vitro, during the intestinal phase, TGs were hydrolyzed more in the MPL emulsion than in the SPL emulsion (decremental AUCs were 1750%/min vs. 180%/min; P < 0.01). MPLs enhance lipid intestinal hydrolysis and promote more rapid intestinal lipid absorption and sharper kinetics of lipemia. Conclusions: Postprandial lipemia in mice can be modulated by emulsifying with MPLs compared with SPLs, partly through differences in chylomicron assembly, and TG hydrolysis rate as observed in vitro. MPLs may thereby contribute to the long-term regulation of lipid metabolism.